Roland Betancourt, Performing the Gospels in Byzantium: Sight, Sound, and Space in the Divine Liturgy and Gordon P. Jeanes and Bridget Nichols, editors, Lively Oracles of God: Perspectives on the Bible and Liturgy. Issue 2 (25th November 2022) - Homrighausen, Jonathan
Abstract : Roland Betancourt, Performing the Gospels in Byzantium: Sight, Sound, and Space in the Divine Liturgy. Cambridge: Cambridge University Press (2021) Gordon P. Jeanes and Bridget Nichols, editors, Lively Oracles of God: Perspectives on the Bible and Liturgy. Collegeville, MN: Liturgical Press (2022)